Perencanaan Pembangunan : National Debts and Economic Growth using the Coppock Curve : THE CASE OF EMERGING MARKETS - Mohamad Firda Fauzan (Kementerian PPN/Bappenas, 2015)
In the past three decades, average economic growth rate for emerging markets have been fairly above that of world average and debt of Emerging Markets are lower than of Advances Economies.